2018
DOI: 10.1111/mms.12555
|View full text |Cite
|
Sign up to set email alerts
|

Demography and genetics suggest reversal of dolphin source‐sink dynamics, with implications for conservation

Abstract: The forecast for the viability of populations depends upon metapopulation dynamics: the combination of reproduction and mortality within populations, as well as dispersal between populations. This study focuses on an Indo-Pacific bottlenose dolphin (Tursiops aduncus) population in coastal waters near Bunbury, Western Australia. Demographic modeling of this population suggested that recent reproductive output was not sufficient to offset mortality. Migrants from adjacent populations might make up this deficit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…Adult females in the inner estuary of the Gulf of Guayaquil have higher residence level and smaller home ranges than males (Félix et al, 2019a), which has also been observed in other bottlenose populations elsewhere (Wells et al, 1987;Möller and Beheregaray, 2004;Sprogis et al, 2015). However, higher dispersal rate by females has been reported in bottlenose dolphins in Scotland (Natoli et al, 2005) and in the Indo-Pacific bottlenose dolphin from Western Australia (Manlik et al, 2019), apparently driven by habitat quality, hence selective emigration cannot be ruled out as a potential explanation to what occurred with these two dolphin communities in our study area.…”
Section: Discussionsupporting
confidence: 55%
“…Adult females in the inner estuary of the Gulf of Guayaquil have higher residence level and smaller home ranges than males (Félix et al, 2019a), which has also been observed in other bottlenose populations elsewhere (Wells et al, 1987;Möller and Beheregaray, 2004;Sprogis et al, 2015). However, higher dispersal rate by females has been reported in bottlenose dolphins in Scotland (Natoli et al, 2005) and in the Indo-Pacific bottlenose dolphin from Western Australia (Manlik et al, 2019), apparently driven by habitat quality, hence selective emigration cannot be ruled out as a potential explanation to what occurred with these two dolphin communities in our study area.…”
Section: Discussionsupporting
confidence: 55%
“… Microsatellite diversity measures based on the BB maximum sampling approach are from Manlik et al (). …”
Section: Resultsmentioning
confidence: 99%
“… MHC DNA sequence alignment available in Dryad/Figure (Manlik et al, ; https://doi.org/10.5061/dryad.73k278d). Microsatellite data: previously uploaded in supplement of published article (Manlik et al, ): https://doi.org/10.1111/mms.12555. Additional microsatellite data now in Dryad/Table , available from the Dryad Digital Repository: Manlik et al () https://doi.org/10.5061/dryad.73k278d. Various other data available in Dryad/Appendix ( https://doi.org/10.5061/dryad.73k278d; Manlik et al, ), including: conservative sampling design and numbers (Table ), MHC and microsatellite diversity measures, including F ST (Table ), BLASTN results (Table ), diversity measures and statistics for microsatellite subsamples (Table ). …”
Section: Data Accessibilitymentioning
confidence: 99%
“…Low reproductive rates have been identified as the leading cause for the decline (Manlik et al., ). Historically, the Bunbury dolphin population has served as a “source” population for the larger meta‐population along the southwestern Australian coast (Manlik et al., In Press), and more recently, the abundance and temporary emigration of the population are also influenced by climate variability (Sprogis, Christiansen, Wandres, & Bejder, ), thus raising additional conservation concerns for the overall meta‐population viability. Therefore, it is important to understand both the ability to detect trends in population abundance and to quantify demographic parameters for this population to best inform management.…”
Section: Introductionmentioning
confidence: 99%